Romance languages and linguistic theory 2018 selected papers from 'Going Romance' 32, Utrecht - Baauw, Sergio, 1970-; Drijkoningen, Frank (Franciscus Alphonsus Coenraad), 1956-; Meroni, Luisa (Amsterdam studies in the theory and history of linguistic science. Series IV, Current issues in linguistic theory,, 2021)
"This volume contains a peer reviewed selection of invited contributions, papers and posters that were presented at the December, 2018 venue of Going Romance (XXXII) in Utrecht (a four day program that included two thematic workshops). The papers all discuss data and formalized analyses of one or more Romance languages or dialects, in either synchronic or diachronic perspective, and pay particular attention to the variation and the actual variability that is at stake, not only in syntax and morpho-syntax but also in semantics and phonology. Beyond the discussion of differences between languages and/or dialects from a formalist perspective, the volume also contains a number of papers linking the theme of variation to sociolinguistic issues such as natural bilingualism and micro-contact"--